Identifikasi Faktor Penyebab Rendahnya Kemampuan Numerasi Siswa (Studi Kasus pada Siswa Kelas IV SDN 8 Cakranegara) - Witono, Hari; Wahyuningsih, Baiq Yuni (Darul Yasin Al Sys, 2024)
This research aims to describe the factors causing low numeracy skills in mathematics subjects in class 4 of SDN 8 Cakranegara. Considering that nowadays problems in learning mathematics are very often encountered and varied. Because in learning mathematics there are many symbols, numbers and formulas so it is often considered difficult and boring, therefore there are still many students who do not understand the concepts from mathematics lessons to their application in everyday life. This research uses qualitative methods with a library research approach. The results of the research show that the difficulties in learning mathematics experienced by students show that there are two influencing factors, namely internal factors and external factors. Internal factors that influence include attitudes towards learning, motivation to learn, and body health. Meanwhile, external factors include variations in teacher teaching, family and social environment.